Asuhan Keperawatan Tn.”A” Dengan Gangguan Sistem Perkemihan: Post Operasi Prostatektomy - Sarma Eko Natalia Sinaga; Dian Harumawati Putri (Jurnal Obstretika Scientia, 2014)
The purpose of writing this Case Study is to be able to implement nursing care directly to Mr. "A" with the urinary system disorders: Post Prostatectomy Surgery. From the results of the assessment data obtained is pain in the surgical wound, a pain scale of 4 out of 10 (range 0-10), wound drain wet look, there are seven stitches, client was installed urinary catheter irrigation, clear urine, BP: 120/80mmHg, temperature 37,3 ° C, pulse 98x/minutes, the client said that he has never taken a shower during the treatment (5 days), the client said that he did not know about his illness. Emerging diagnosis: elimination disorders b/d surgical procedures, pain b/d tissue dissolution, risk of infection b/d the presence of surgical incision wound, self-care deficit b/d of physical weakness. The planning and the implementation of nursing were tailored to the needs of the patient. In the evaluation of diagnostic disorders the pattern of elimination disorders was partially resolved, the pain was resolved on the 3rd day, the risk of infection was resolved on 4th day, self-care deficit was resolved on the 2nd day, and lack of knowledge was overcome on the 1st day.